The Relationship between Motor Function and Behavioral Function in Infants with Low Birth Weight - AMINI, Malek; ALIABADI, Faranak; ALIZADE, Mehdi; KALANI, Majid; QORBANI, Mostafa (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Amini M, Aliabadi F, Alizade M, Kalani M, Qorbani M. The Relationship between Motor Function and Behavioral Function in Infants with Low Birth Weight. Iran J Child Neurol. Autumn 2016; 10(4):49-55. Abstract Objective Nowadays, the evaluation of all aspects of infant development is important. However, in practice, some of these assessments, especially those requiring more manipulation on high-risk infants, may impose additional stress on them. Therefore, sometimes it is essential to utilize the results of a developmental assessment for the prediction of some other aspects of development. This study evaluated the relationship between the scores of the behavioral tests and the motor function test. Materials & Methods This cross-sectional study and was undertaken in the Neonatal Intensive Care Center and Clinic of Shahid Akbar Abadi Hospital, Tehran, Iran. A group of 50 infants with low birth weights was selected based on the easy non-contingency method and the inclusion criteria, and served as the participants. In order to assess the motor function and the behavioral performance, the motor function test (a test of infant motor performance (TIMP)) and the neonatal behavioral assessment scale (neonatal behavioral assessment scale (NBAS)) were used respectively. TIMP has both stimulation and observation sections. The items include habituation, social interaction, motor system, state organization, state regulation, autonomic system, smile, supplementary items, and the reflex. Results No significant association was found between the items of the habituation of behavioral testing and the observation of the movement test. There was no statistically significant relationship between the habituation and stimulation sections as well as between the system autonomous of the behavioral test and the observation section of the motor test (P>0.05). The relationship between other variables was statistically significant (P<0.05). Conclusion The scores of some behavioral performance items could be a good predictor of the scores of the motor function items for low birth weight infants in the neonatal period. References 1. Wright-Ott C. Mobility. In: Case-smith J, editors. Occupational Therapy for Children. 5th ed. USA: Mosbey; 2005.P. 657-684. 2. Case-smith J. Fine motor outcomes in preschool children who receive occupational therapy services. Am J Occup Ther 1996;50(6):466-74. 3. Soleimani F, Zaheri F, Abdi F. Long-term neurodevelopmental outcomes after preterm birth. Iran Red Crescent Med J 2014;16(6):1-8. 4. Hunter JG. Neonatal Intensive Care Unite. In: Case-smith J, editors. Occupational Therapy for Children. 5th ed. USA: Mosbey; 2005.P. 688-754. 5. Arpino C, Compagnone E, Montanaro ML, Cacciatore D, De Luca A, Cerulli A, Di Girolamo S, Curatolo P. Preterm birth and neurodevelopmental outcome: a review. Childs Nerv Syst 2010;50:10-20. 6. Pedersen SJ, Sommerfelt K, Markestad T. Early motor development of premature infants with birthweight less than 2000 grams. Acta Pediatr 2000;89:1450-61. 7. Aliabadi F, Amini M, Alizade M, Kalani M, Qorbani M. Prediction of infant motor performance through performance evaluation of behavior. J Modern Rehab 2011;5 (3): 54-59. 8. Orton J, Spittle A, Doyle L, Anderson P, Boyd R. Do early intervention programs improve cognitive and motor outcomes for preterm infants after discharge: a systematic review. Dev Med Child Neurol 2009;51(11):851-9. 9. Spittle AJ, Doyle LW, Boyd RN. A systematic review of clinimetric properties of neuromotor assessment for preterm infants during the first year of life. Dev Med Child Neurol 2008;50(10):254-66. 10. Brazeltone B. Neonatal Behavioral Assessment Scale. 3rd ed. University of Masschusetts and Harvard Medical School: Mac Keit Press; 1995. 8-10, 67, P. 104-5. 11. Falk B, Eliakim A, Dotan R, Liebermann DG, Regev R, Bar-Or O. Birth weight and physical ability in 5- to -8-yr old healthy children born prematurely. Med Sci Sports Exerc 1997;29(9):1124-30. 12. Burns Y, O’Callaghan M, McDonell B, Rogers Y. Movement and motor development in ELBW infant at 1 year is related to cognitive and motor abilities at 4 years. Early Hum Dev 2004;80:19-29. 13. Tavasoli A, Aliabadi F, Eftekhari R. Motor Developmental Status of Moderately Low Birth Weight Preterm Infants. Iran J Pediatr 2014;24 (5), 581-586. 14. Islam M. The Effects of Low Birth Weight on School Performance and Behavioral Outcomes of Elementary School Children in Oman. Oman Med J 2015;30(4):241-51. 15. Ohgi S, Arisawa K, Takahashi T, Kusumoto T, Goto Y, Akiyama T, Saito H. Neonatal behavioral assessment scale as a predictor of later developmental disabilities of low-birth weight and/or premature infants. Brain Dev 2003;25:313-21. 16. Ho YB, Lee RS, Chow CB, Pang MY. Impact of massage therapy on motor outcomes in very low-birth weight infants: Randomized controlled pilot study. Pediatr Int 2010; 52(3):378-85. 17. Craciunoiu O, Holsti L. A Systematic Review of the Predictive Validity of Neurobehavioral Assessments During the Preterm Period. Phys Occup Ther Pediatr 2016; 17:1-16. 18. Tirosh E, Abadi J, Berger A, Cohen A. Relationship between neonatal behavior and subsequent temperament. Acta Pediatr 1992;81(8):29-31.